PETROGRAPHY AND MINERAL CHEMISTRY OF THE RELIEGOS CHONDRITE - Lozano R.P.; Martin-Crespo T. (My University, 2004)
The Reliegos meteorite is an L5 ordinary chondrite. The chondrules are embedded in a fine-grained matrix that predominantly consists of olivine and orthopyroxene, with accessory clinopyroxene, troilite, apatite, and a mesostasis of feldspar composition. The metal phase is predominantly kamacite with subordinate taenite and traces of native Cu. The bulk composition of Reliegos compares well with other L5 chondrites, except for a distinctly lower Cr content. A Cr-rich object has been identified, which shows a concentric mineral and chemical zoning and is composed mainly of chromite and plagioclase, with minor amounts of merrillite and Mg, V-rich ilmenite.